Oral administration of pyrophosphate inhibits connective tissue calcification - Dóra Dedinszki; Flóra Szeri; Eszter Kozák; Viola Pomozi; Natália Tőkési; Tamás Róbert Mezei; Kinga Merczel; Emmanuel Letavernier; Ellie Tang; Olivier Le Saux; Tamás Arányi; Koen van de Wetering; et al. (EMBO Molecular Medicine)
Abstract Various disorders including pseudoxanthoma elasticum (PXE) and generalized arterial calcification of infancy (GACI), which are caused by inactivating mutations in ABCC6 and ENPP1, respectively, present with extensive tissue calcification due to reduced plasma pyrophosphate (PPi). However, it has always been assumed that the bioavailability of orally administered PPi is negligible. Here, we demonstrate increased PPi concentration in the circulation of humans after oral PPi administration. Furthermore, in mouse models of PXE and GACI, oral PPi provided via drinking water attenuated their ectopic calcification phenotype. Noticeably, provision of drinking water with 0.3 mM PPi to mice heterozygous for inactivating mutations in Enpp1 during pregnancy robustly inhibited ectopic calcification in their Enpp1−/− offspring. Our work shows that orally administered PPi is readily absorbed in humans and mice and inhibits connective tissue calcification in mouse models of PXE and GACI. PPi, which is recognized as safe by the FDA, therefore not only has great potential as an effective and extremely low‐cost treatment for these currently intractable genetic disorders, but also in other conditions involving connective tissue calcification.